2010
DOI: 10.3390/ma3094668
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Behavior of Individual Vascular Smooth Muscle Cells Assessed By Lateral Force Microscopy

Abstract: With the advancement of the field of biotribology, considerable interest has arisen in the study of cell and tissue frictional properties. From the perspective of medical device development, the frictional properties between a rigid surface and underlying cells and tissues are of a particular clinical interest. As with many bearing surfaces, it is likely that contact asperities exist at the size scale of single cells and below. Thus, a technique to measure cellular frictional properties directly would be benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This value is very close to a value measured with a spherical AFM probe using similar scan conditions but on different kind of cells, i.e. vascular smooth muscle cells, that was found to be approximately 0.06 (Dean et al ., ). Taking μ = 0.06, one obtains the value of shear stress at the level of τ = 13 Pa.…”
Section: Discussionmentioning
confidence: 97%
“…This value is very close to a value measured with a spherical AFM probe using similar scan conditions but on different kind of cells, i.e. vascular smooth muscle cells, that was found to be approximately 0.06 (Dean et al ., ). Taking μ = 0.06, one obtains the value of shear stress at the level of τ = 13 Pa.…”
Section: Discussionmentioning
confidence: 97%
“…This imaging technique has been established by material scientists to detect, for example, charge distributions on nonbiological surfaces. 48 Although the physicochemical characterization of biological samples by AFM is less frequently reported, [49][50][51] we selected this method because the direct detection of cell-bound COSs by fluorescence microscopy failed (data not shown). AFM enabled us to measure an increased friction between the scanning probe and the endothelial cell surface after treatment with COSs (Figure 2A lateral deflection image).…”
Section: Discussionmentioning
confidence: 99%
“…32,42,68, On the right side of the figure are shown the FFM studies using a colloidal probe made from: collagen; 96 latex; 97 polyethylene (PE); 25,28,45,98 polyethylene glycol (PEG); 99 poly(methyl methacrylate) PMMA; 26,27,95,100 polystyrene (PS); 33,71,101 cellulose; 31,[102][103][104][105][106][107][108][109] and silica. 35,36,98,[110][111][112][113][114][115][116][117] The volume of the symbol corresponds to the number of studies using the specific system of materials. Colloidal probes of the same material are in groups, while the green-shaded area represents the knowledge gap on friction between soft surfaces that requires future research attention.…”
Section: Effect Of Surface Interactions On Nanoscale Frictionmentioning
confidence: 99%
“…For instance, FFM employing a borosilicate colloidal probe was used to study the frictional behaviour of individual vascular smooth cells. 110 It revealed that µ was increased with increasing cellular crosslinking and decreased by cytoskeletal polymerization, which could be used to improve the design in applications of intravenous devices such as stents and heart valves. Furthermore, by directly measuring friction on cells, one could better understand the disorder related to stresses in cells, such as diagnosis of heart diseases.…”
Section: Cellsmentioning
confidence: 99%